Chemical state tuning of surface Ce species on pristine CeO2 with 2400% boosting in peroxidase-like activity for glucose detection. Issue 57 (11th June 2020) - Zhang, Jieru; Tan, Zicong; Leng, Wanying; Chen, Yu-Cheng; Zhang, Shiqing; Lo, Benedict T. W.; Yung, Ken Kin Lam; Peng, Yung-Kang
Abstract : 2400% increase in CeO2 peroxidase-like activity can be easily achieved on the (100) surface due to the promoted H2 O2 adsorption/activation. Abstract : We demonstrate that the Ce reactivity of CeO2 towards H2 O2 is dictated by its local structure and electron density. More than 2400% increase in peroxidase-like activity has been achieved on the (100) surface for glucose detection due to the promoted H2 O2 adsorption and subsequent activation by the electron-rich Ce species.